2021
DOI: 10.5624/isd.20200230
|View full text |Cite
|
Sign up to set email alerts
|

CBCT imaging and histopathological characteristics of osteoradionecrosis and medication-related osteonecrosis of the jaw

Abstract: Purpose The purpose of this study was to evaluate the cone-beam computed tomographic (CBCT) imaging and histopathological characteristics of osteoradionecrosis (ORN) and medication-related osteonecrosis of the jaw (MRONJ). Materials and Methods Ten surgical specimens from segmental mandibulectomy (3 ORN and 7 MRONJ) were analyzed using CBCT. The CBCT parameters were as follows: high-resolution mode (tube voltage, 90.0 kV; tube current, 4.00 mA; rotation time, 16.8 s; fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…According to Simpione et al (2020) and Kim et al (2020), the most frequent alterations are bony sequestrum, bone exposure, and osteosclerosis. In the study by Ogura et al (2021), in addition to CBCT images, histopathology was also used to identify the main microscopic features of MRONJ, including necrotic bone, granulation tissue surrounded by bone and inflammatory cells; osteoclasts are rarely found around the necrotic bone, but were seen on its surface, in contact with the granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…According to Simpione et al (2020) and Kim et al (2020), the most frequent alterations are bony sequestrum, bone exposure, and osteosclerosis. In the study by Ogura et al (2021), in addition to CBCT images, histopathology was also used to identify the main microscopic features of MRONJ, including necrotic bone, granulation tissue surrounded by bone and inflammatory cells; osteoclasts are rarely found around the necrotic bone, but were seen on its surface, in contact with the granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The CBCT parameters at our hospital were as follows: standard mode (tube voltage, 90.0 kV; tube current, 4.00 mA; rotation time, 16.8 s; field of view, 81 mm × 81 mm; thickness, 0.144 mm), high-density mode (tube voltage, 90.0 kV; tube current, 4.00 mA; rotation time, 33.5 s; field of view, 81 mm × 81 mm; thickness, 0.144 mm), and high-resolution mode (tube voltage, 90.0 kV; tube current, 4.00 mA; rotation time, 16.8 s; field of view, 56 mm × 56 mm; thickness, 0.099 mm) [ 25 ]. High-resolution mode was sharper than both standard mode and high-density mode for the analysis of surgical specimens in segmental mandibulectomy [ 26 ]. However, standard mode was used for patients as the oral and maxillofacial protocols at our hospital because evaluation of another dentomaxillofacial lesion was necessary for diagnosis and treatment planning in dental practice [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ogura et al . [ 20 ] showed that surgical specimens from segmental mandibulectomy of MRONJ were analysed using cone-beam computed tomography (CBCT), and CBCT could be useful for the post-surgical evaluation of MRONJ. Miyashita et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, maximum SUVs for MRONJ (n = 4, 25.4 ± 4.9) and chronic osteomyelitis (n = 3, 14.6 ± 3.1) in mandible were higher than those of the opposite side as normal mandible (3.8 ± 0.7 and 4.6 ± 1.8, respectively). Furthermore, Ogura et al [20] showed that surgical specimens from segmental mandibulectomy of MRONJ were analysed using cone-beam computed tomography (CBCT), and CBCT could be useful for the post-surgical evaluation of MRONJ. Miyashita et al [5] indicated that 3D SPECT/CT is useful not only for detecting jaw bone invasion of oral cancer but also for surgical planning.…”
Section: Discussionmentioning
confidence: 99%